ANTARA LAPAR DAN BERKURBAN: KISAH EMPAT BRAHMANA DALAM GEGURITAN YADNYA RING KURUKSETRA - I Wayan Juliana (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2023)
Geguritan Yadnya ring Kuruksetra is a literary work that has the tendency to be read continuously. This work not only tells how a mouse turns golden yellow, but the life stories of four brahmins are important to read in the midst of a large and lavish Hindu ceremony. Research on geguritan yadnya ring kuruksetra on this occasion was conducted to see the ideology that underlies it. Even though this work is classified as a short work of geguritan, when examined it has a very deep moral message. The ideology of geguritan yadnya ring kuruksetra is kalascaryan (sincerity). The kalascaryan is shown by four brahmins who really know their dharma and swadharma. Keywords:Ideology, Balinese Literature, Dharma, Lascarya.